Introductory Chapter: Demographic Analysis - Andrzej Klimczuk (Demographic Analysis: Selected Concepts, Tools, and Applications, 2021)
Demography is typically defined as the study of human populations and the changes in their quantity associated with migration, fertility, and mortality. The term demography comes from Greek word and means “describing people.” Thus, this discipline deals with the characteristics of the population, taking into account features such as, sex ratio, age structure, composition, spatial distribution, and population density. In addition, sometimes a distinction is made between “formal demography” or “demographic analysis,” which includes the statistical analysis of population parameters and their dynamics, and “population studies,” that is, the analysis of the causes and effects of changes in the structure of the population in a broader context and in connection with other phenomena and processes.
Keywords: J10; R23; 330; statistical studies; family structure; population; migration; public health; ageing; demography